BULLYING AS A BARRIER TO EMOTIONAL INTELLIGENCE DEVELOPMENT IN PRIMARY SCHOOL CHILDREN - Berdiyeva Gulmira Juraevna; Babadjanova Oʻgʻiljon Azim qizi (The Conference Hub, 2025)
This scientific article analyzes the relationship between bullying and the development of emotional intelligence in primary school children. While emotional intelligence (EI) is considered a critical factor in fostering empathy, self-awareness, and prosocial behavior, bullying interrupts and often reverses this process. The article defines the key components of emotional intelligence in young learners and discusses how persistent exposure to bullying—either as a victim or perpetrator—affects children's emotional regulation, interpersonal trust, and mental well-being. Drawing on empirical research and real-life case studies, the article explores how bullying negatively impacts neural and psychological pathways associated with emotional maturity. Furthermore, it provides a comprehensive set of strategic interventions, including curriculum integration, parental training, emotional coaching, and school-wide reform programs designed to enhance both anti-bullying efforts and emotional intelligence education. The study concludes that addressing emotional intelligence and bullying simultaneously is essential for ensuring a healthy, inclusive, and developmentally supportive school environment.
Keywords: bullying, emotional intelligence, primary school children, empathy, emotional development, psychological resilience, school environment.